BS EN 62841-2-1 AMD AC. Electric motor-operated hand-held tools, transportable tools and lawn and garden machinery. Safety. Part 2-1. Particular requirements for hand-held drills and impact drills (17th July 2020) - British Standards Institution,
No abstract available